Kinetics and mechanism of methylene blue removal by electrosynthesized ferrate(VI). Issue 11 (23rd July 2016) - Turkay, Ozge; Barışçı, Sibel; Dimoglo, Anatholy
ABSTRACT: The oxidation of methylene blue (MB) by electrosynthesized ferrate(VI) in a semi-batch reactor is investigated. The effects of pH, Fe(VI) dose and initial MB concentration on the efficiency of the degradation process were studied. The original pH of MB solution was found more effective on the degradation and colour removal as 96.82% MB removal and 40.36% colour removal were gained. Initial MB solution and Fe(VI) dose affected the removal efficiencies. Degradation of MB by Fe(VI) was the second-order reaction kinetics. The density functional theory (DFT) analysis confirmed that density is intended mostly on the phenyl rings and least of all on the bonding orbitals of the middle heterocycle of МВ.